2020
DOI: 10.1016/j.socscimed.2020.113247
|View full text |Cite
|
Sign up to set email alerts
|

Association between provincial income levels and drug prices in China over the period 2010–2017

Abstract: In the past decade, the Chinese central government has made sweeping reforms to national pharmaceutical policies. However, provincial authorities have retained control over most drug procurement procedures, potentially leading to cross-province differences in drug prices. The objectives of this study were to (i) examine drug price trends in 31 Chinese provinces and municipalities between 2010 and 2017; (ii) evaluate the association between provincial income levels and drug prices over this period; and (iii) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For example, in 2018, China's total drug expenditure was 1,914.89 billion yuan, accounting for 32.39% of the total health expenditure, which is far higher than the average of 17% in OECD countries ( 51 ). In addition, the results of a survey on drug prices in 31 Chinese provinces showed that drug prices in Heilongjiang province, the area we investigated, were generally higher than the national average ( 52 ). He et al and Zeng et al believe that this is related to the high price and quantity of drugs used ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 82%
“…For example, in 2018, China's total drug expenditure was 1,914.89 billion yuan, accounting for 32.39% of the total health expenditure, which is far higher than the average of 17% in OECD countries ( 51 ). In addition, the results of a survey on drug prices in 31 Chinese provinces showed that drug prices in Heilongjiang province, the area we investigated, were generally higher than the national average ( 52 ). He et al and Zeng et al believe that this is related to the high price and quantity of drugs used ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, we take INN as the molecular boundary. Second, drug bidding and procurement is mainly carried out by provincial units in the Chinese mainland, and there are significant differences in the drug market among provinces ( Shi et al, 2020 ). Therefore, we set province/city as the geographical boundary.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of this policy, insured persons have access to reimbursement for negotiated medicines, which improves cost-effectiveness, and thereby reduces the burden ( 9 , 10 ). Since the implementation of the National Drug Policy, drug prices have been reduced by an average of 60.1%, reducing the burden on patients by >$90 billion ( 11 ).…”
Section: Introductionmentioning
confidence: 99%